Tratamento para transtorno do estresse pós-traumático com a técnica emdr® (eye movement desensitization and reprocessing): seus efeitos nos aspectos psicológicos, cognitivos e na arquitetura do sono - Raboni, Mara Regina [UNIFESP] (2010)
Post traumatic stress impacts on cognition, mood and sleep pattern. These changes take place in differing intensities and depend on pre existing mental an physical conditions of the individual. The aim of this investigation was to study these functions in post traumatic stress disorder patients, victims of assaults and kidnapping, before and after eye movement desensitization reprocessing psychotherapy treatment (EMDR), for an average of five sessions. Twenty nine individuals (12 PTSD patients, 7with trauma without PTSD and 10 mentally healthy controls) participated in this study. Objective (polysomnography study) and subjective (Pittsburg sleep questionnaire) sleep assessments and psychological (anxiety, stress, depression, and quality of life) and cognitive (memory, executive functions) assessments were carried out, before and after the psychotherapeutic treatment. The analysis of baseline sleep pattern showed that PTSD patients spent more time awake after sleep onset (WASO) and had lower sleep efficiency than controls. Before the onset of treatment, all PTSD patients had more subjective complains regarding their quality of life, regarding anxiety disorders, stress and mood than controls. After treatment sleep and psychological aspects improved to control levels. Similarly to sleep and mood problems, PTSD patients showed a worse performance in cognitive tasks that asses longterm verbal and non-verbal memory and executive function. These results emphasize that EMDR psychotherapy is specific for trauma and promotes the recovery of neurobiological functions close to the levels found in healthy subjects.